On solving boundary value problems associated with generalised LQ control of 2-D systems - Ntogramatzidis, Lorenzo; Cantoni, M. (Lavoisier SAS, 2009)
This paper considers the bounded-frame linear quadratic (LQ) optimal control problem for Roesser models with double-ended constraints on the horizontal and vertical semistates. Necessary and sufficient conditions for optimality are presented for this problem. We also identify and discuss situations in which it is possible to compute the optimal control law from these conditions.